China and East Asia after the Wall Street crisis - Lam, Peng Er 1959-; Qin, Yaqing 1953-; Yang, Mu (Series on contemporary China, 2013)
This book examines the need for greater East Asian cooperation and the challenges to this grand endeavor. With differing national outlooks, how can East Asia preserve peace, prosperity and stability amidst geopolitical competition? To answer this question, the volume examines the political and economic relations between Beijing and its neighbors against the backdrop of two trends: the power shift from the West to the East in the aftermath of the American Financial Crisis and the rise of China